Evaluation of power flow techniques for personal computers - Keyhani, A.; Abur, A.; Hao, S. (IEEE transactions on power systems, 1989)
An evaluation study is presented for running power flow programs on an IBM/AT personal computer (PC). Different issues that have been the subject of discussion for the mainframe computer implementation are addressed regarding the PC applications. These include convergence rates, iteration counts, memory requirements, effects of low precision arithmetic, ill conditioning, and the CPU times. A number of formulations of the power flow problem are considered and compared with regard to the mentioned issues. The investigated formulations are: the full Newton-Raphson power flow, the fast decoupled power flow, the Gauss-Seidel flow, and the second-order power flow using cartesian coordinates. The numerical results of running power flow studies for the IEEE 5, 14, 30, 57 and 118 bus test systems are presented and discussed.< >